Zmiana paradygmatu zarządzania w ekoempatycznej koncepcji menedżeryzmu - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2009)
The negative tendencies in contemporary society and organisations occur as a result of technocratic culture (technopoly). To improve this situation, it is necessary to change the technocratic decision-making paradigm to an ecoempathetic one. The paper presents the ecoempathetic concept of management operations as a philosophy leading to sustainable development and harmony in organisations.